Diseño de un Sistema de Contabilidad de Costos por Órdenes de Producción en la Mueblería y Ebanistería Pepe Lucho de la Ciudad de Yantzaza, Periodo Enero-Marzo del 2014 - Olmedo Salinas, Maritza Alexandra (2016)
This thesis entitled "DESIGNING A SYSTEM OF COST ACCOUNTING FOR ORDERS PRODUCTION IN THE FURNITURE INDUSTRY AND EBANISTERÍA PEPE LUCHO CITY Yantzaza, PERIOD JANUARY-MARCH 2014" general rules for graduation was built on issued by the National University of Loja, as a prerequisite to obtaining of Engineering degree in Accounting and Auditing requirement. In order to comply with the goals outlined in this thesis, the plan and manual account that was used to develop the accounting process was developed; inventory of goods in physical form was performed, confirming the presence of existing products for sale; the accounting process was carried out, building and auxiliary accounting records according to the needs of the furniture and joinery PEPE LUCHO who admitted establish its development from the initial inventory, to the financial statements, which reflect the results obtained in this period. He introduced himself and the financial statements are analyzed through Financial Analysis and Indicators to evaluate the Financial, Economic and Operational Company performance to facilitate decision-making, obtaining as results the company has a positive value to meet their obligations with third parties having no risk of disability payments.